Isolation, Culture, and Maintenance of Mouse Intestinal Stem Cells - Kevin O’Rourke; Sarah Ackerman; Lukas Dow; Scott Lowe (Bio-Protocol, 2016)
In this protocol we describe our modifications to a method to isolate, culture and maintain mouse intestinal stem cells as crypt-villus forming organoids. These cells, isolated either from the small or large intestine, maintain self-renewal and multilineage differentiation potential over time. This provides investigators a tool to culture wild type or transformed intestinal epithelium, and a robust assay for stem cell tissue homeostasis in vitro.